تطوير إطار مرجعي لوضع معايير تقييم العروض خاص بمشروعات التصميم - بناء - حمد, ابتسام; مصطفى, ماهر; علي, كنز (Latakia University Journal -Engineering Sciences Series, 2019)
In the last decades, great efforts have been made in developing methods of selecting contractors for implementation of construction projects. However, a small number of researches have highlighted the evaluation of proposals in design-build projects. It is for this reason that the methodologies and methods currently used by governmental and non-governmental bodies worldwide in evaluating proposals for design - build projects have many shortcomings and are in urgent need of improvement. The study examined the different practices of proposals evaluation in design - build projects, identifying their weaknesses, and then improvement the process of selecting the most capable contractor of implementing the design-build project, by developing reference framework to evaluate proposals in this type of projects. بذلت في العقود الماضية جهود كبيرة على مستوى العالم في مجال تطوير أساليب اختيار المقاولين لتنفيذ مشروعات التشييد، ومع ذلك فإن عدداً قليلاً من الأبحاث المنجزة في هذا المجال سلطت الضوء على تقييم العروض في مشروعات التصميم-بناء ، ولهذا السبب تحمل المنهجيات والطرق المتبعة حالياً من قبل الهيئات الحكومية وغير الحكومية على مستوى العالم في مجال تقييم العروض لمشروعات التصميم-بناء الكثير من أوجه القصور وهي بحاجة ماسة للتحسين. تم في هذا البحث دراسة الممارسات المختلفة لتقييم العروض في مشروعات التصميم-بناء وتحديد نقاط ضعفها ومن ثم المساهمة في تطوير عملية اختيار المقاول الأقدر على تنفيذ مشروع التصميم-بناء من خلال تطوير إطار مرجعي لتقييم العروض في هذا النوع من المشروعات.